Autism: Educational Assessment and Intervention, a Speech Therapy Perspective (REVISTA CIENTÍFICA SIGNOS FÓNICOS, 2021)
INTRODUCTION: The assessment and correct intervention of the reading and writing processes is important for the development of social, behavioral, linguistic and communicative skills so that the child can function more easily in their environment. METHODS: PRISMA systematic review. Methodology referring to the exploration of a minimum set of elements, based on evidence. RESULTS: This review made it possible to show different available resources taking into account the variables: evaluation methods, intervention strategy, learning and Autism, having as reference 60 articles related to the object of study. ANALYSIS AND DISCUSSION: Early evaluation and intervention contribute greatly to the reduction of symptoms and increase the child's ability to grow and learn new skills. CONCLUSIONS: Both the evaluation methods and the intervention strategies used for reading and writing in children diagnosed with autism must be adapted to their characteristics.
Keywords: Learning; Autistic Disorder; Assessment; Early Educational Intervention; Learning Difficulties